PERAN PONDOK PESANTREN DALAM PENGEMBANGAN KULTUR ISLAM NUSANTARA - Sunarto, Sunarto (Universitas Islam Negeri Raden Intan Lampung, 2015)
Islamic Shari'a in the life of the state provide clear guidance in addressing the infidels (non-Muslims) and be fair to them according to sharia scales so that the Muslims are also protected from bad influences them. Among the provisions of Islam on infidels are as follows Islam does not compel a heathen was to convert to Islam. Therefore, in the future reign of the first four caliphs of Islam, the unbelievers who live under his rule remains protected his blood, even though they still choose his religion other than Islam. As for the fight is not solely due to choose a religion other than Islam. They fought because of hostility and their opposition to Islam. In Islam there are four kinds of infidels, and each get a different treatment, namely: Kafir dhimmi, mu'ahad Kafir, Kafir musta'man, Kafir harbi. Islamic Studies (Islamic studies) is a discipline / study that puts Islam not only in the context of theological normative (doctrinal), but also puts Islam as part of the historical and actual phenomena (empirical). That means, Islam is not only understood or analyzed from a normative dimension but also a theological-historical and actual dimensions. For that, the study approach used likewise vary in accordance with Characteristics of Islam itself.